Do children need a longer time to shed SARS-CoV-2 in stool than adults? - Xiang Ma; Liang Su; Yunkui Zhang; Xiuzhen Zhang; Zhongtao Gai; Zhongfa Zhang (Journal of Microbiology, Immunology and Infection, 2020)
SARS-CoV-2 can be shed in the stool of patients in the recovery phase. Children show a longer shedding time than adults. We analyzed the possible causes of this finding and recommend that a negative stool sample be included in a patient's discharge criteria.